Reconstruction of Forest Area Land Tenure in the Perspective of Maqashid Sharia (Hifz Al-Mal) in Ngadirenggo Village, Wlingi District, Blitar Regency - Rizky Rendyana Firmansyah; Diyan Isnaeni; Moh. Muhibbin (Fakultas Syariah IAIN madura, 2025)
Conflicts over forest land ownership in Indonesia continue to recur due to the lack of synchronization between the agrarian and forestry regimes. This overlapping authority creates legal uncertainty and impacts the protection of the economic rights of communities living in and around forest areas. This situation occurs in Ngadirenggo Village, Wlingi District, Blitar Regency, where tensions between the community and Perhutani regarding the control and utilization of forest crops continue. This study aims to analyze the legal regulations for forest land ownership based on applicable laws and regulations in Indonesia and reconstruct its ownership policy from the perspective of maqashid sharia, specifically hifz al-mal, to support sustainable development in Ngadirenggo Village. The study used an empirical juridical method with a qualitative descriptive approach to examine the process of law working in society. The results of the study indicate that regulations on land ownership in forest areas have not been harmoniously integrated, giving rise to policy dualism and prolonged conflict. Policy reconstruction is directed at strengthening the recognition of local community rights, harmonizing agrarian and forestry regulations, strengthening land ownership resolution mechanisms, and orienting policies towards sustainable development that balances economic, social, and environmental aspects. In the perspective hifz al-mal, the policy update emphasizes certainty and protection of the results of community efforts without ignoring the sustainability of the ecological function of forest areas. The academic contribution of this article lies in integrating the maqashid sharia approach, particularly hifz al-mal, into the discourse of forest land governance and sustainable development, offering a conceptual framework for harmonizing agrarian and forestry policies while strengthening legal protection for local communities in forest areas